PCSK9 in T-cell function and the immune response - Yuying Wang; Xiaosheng Fang; Jiarui Liu; Xiao Lv; Kang Lu; Yingxue Lu; Yujie Jiang (Biomarker Research)
Abstract Proprotein convertase subtilisin/kexin type 9 (PCSK9) was first reported in 2003 and confirmed to be strongly associated with familial hypercholesterolemia. Small-molecule inhibitors targeting PCSK9 provide an effective and safe method for managing hypercholesterolemia and reducing the cardiovascular risk. In recent years, increasing evidence has indicated other important roles for PCSK9 in inflammation, tumors, and even immune regulation. PCSK9 might be an attractive regulator of T-cell activation and expansion. It might mediate inflammation and regulate other types of immune cells. In this review, we summarize the current advances in the field of PCSK9 and provide a narrative of the biological processes associated with PCSK9. The relationships between PCSK9 and different T cells were investigated in depth. Finally, the signaling pathways associated with PCSK9 and the immune response are also summarized in this review.